Design, development and usability testing of an LADM compliant 3D Cadastral prototype system. (November 2020) - Cemellini, Barbara; van Oosterom, Peter; Thompson, Rod; de Vries, Marian
Highlights: Web-based visualization of 3D Cadastral parcels covering both spatial and legal data. A range of interaction options: zoom, 3D rotate, pan, elevate, select, get legal information etc. LADM compliant 3D database at the server side using views on legacy database schema and new 3D tables. Design and development of a standards based prototype with real 3D volumetric and building format parcels. Test data from Brisbane, Queensland, accessible at http://pakhuis.tudelft.nl:8080/edu/Cesium-1.43/Apps/3dcad/ . Abstract: This paper describes research into the design, development and visualization of mixed 2D and 3D Cadastre. A schema has been developed to accommodate this data, with provision for a time component. This paper describes the schema, the visualization requirements, and the provision of LADM-compatible views of the data for the purpose of developing the 3D Cadastral prototype. A significant volume of 2D + t Cadastral data, which also contained 2D + t footprint representations of 3D parcels, is currently incorporated in the Cadastral Database of Queensland. A moderate number of 3D building units, and a smaller number of volumetric parcels have been hand-encoded (from the survey plans), and added to this database. The mixture has been disseminated and displayed in KML through Cesium JS. The visualization of cadastral parcels in 3D is a challenge, since legal boundaries are, in many cases, invisible in the real world; so how can we properly represent something that is not visible to our eyes? This paper uses the results from research looking into problems of occlusion and ambiguous perception (in terms of position, size and shape) of objects in the context of 3D cadastre visualization. The exploration of specific interaction techniques is essential to overcome these issues. After an initial internal usability test (with colleagues/ friends of the developers) our 3D Cadastres web-based dissemination prototype was improved. Next a public usability test is carried out to obtain feedback from different groups of professional users (legal, survey, ICT backgrounds). During the test, the users are asked to perform a series of tasks typical of cadastral systems. Each task is accompanied by a description to give the users some context. Then, each user is asked to reflect on his or her experience. In this paper we present the main results of the public usability test of the 3D Cadastres web-based dissemination prototype.